Knowledge, Attitude and Practice toward Blood Donation among Undergraduate Medical Students of UPUMS, Saifai - Sharma, Ankita; Kariwala, Peeyush; K., Kiran; Mahima; Nayak, Kripashankar; Gupta, Kapil (Indian Journal of Community Health, 2021)
Background: Blood saves millions of life. It cannot be manufactured artificially. Young people are the hope and future of a safe blood supply in the world. So this study was conducted to know the knowledge, awareness and practices among medical students regarding blood donation. Aim & Objective: To study the level of knowledge, attitude and practices about blood donation among undergraduate medical students. To educate the students about blood donation. Settings and Design: The present study was carried out among MBBS students of UPUMS, Saifai. A cross-sectional study was conducted on 452 medical college students. Methods and Material: A pretested, semi-structured questionnaire was used for collecting the necessary information after getting informed consent. Statistical analysis used: Descriptive statistics was used to assess the level of knowledge, attitude and practice. Chi square test was applied to examine the association between knowledge level and other independent variables. Results: A questionnaire based survey among 452 medical students (59.5% males & 40.4% females) regarding blood donation revealed that majority knew about age and weight criteria (57.3% & 67.9% respectively). Of all 93% were willing to donate, while 36% had donated previously; out of which 52.7% had donated more than once. There is significant association between blood donation practice with academic year and gender. Conclusions: The study concludes that many of the students did not have adequate knowledge on blood donation but they have positive attitude towards blood donation. There is a need for education and motivation regarding blood donation through regular CMEs, seminars and campaigns